Intraspecific Adoption and Double Nest Switching in Peregrine Falcons (Falco peregrinus) - Anctil, Alexandre; Franke, Alastair (ARCTIC, 2013)
We describe an observation of post-fledging double nest switching and alloparenting in the Peregrine Falcon (Falco peregrinus tundrius). During the summer of 2010, a 36-day-old male Peregrine Falcon that had been marked with leg bands was seen flying from its natal site and was subsequently observed at a neighboring nest site that contained two nestlings. Motion-sensitive camera images indicated that the adopted nestling remained at the neighboring site for several days, during which time it shared the nest ledge with the two resident nestlings and was fed by the adults that occupied the site. The juvenile falcon subsequently returned to its natal site, where it shared the nest ledge with its natural sibling and received care from its natural parents. This note is the first documentation of nest switching in wild Peregrine Falcons. Nous décrivons l’observation d’un double échange de nids après l’envol et d’alloparents chez le faucon pèlerin (Falco peregrinus tundrius). À l’été 2010, nous avons aperçu un faucon pèlerin bagué âgé de 36 jours en train de s’envoler de son site natal, après quoi nous l’avons observé à un site de nidification avoisinant qui comprenait deux oisillons. Les images de caméras détectrices de mouvement ont indiqué que l’oisillon adopté est resté au site avoisinant pendant plusieurs jours. Pendant ce temps-là, il a partagé la corniche avec les deux oisillons résidents et s’est fait nourrir par les adultes qui occupaient le site. Plus tard, le faucon juvénile a regagné son site natal, où il a partagé la corniche avec l’autre membre de sa fratrie et reçu des soins de ses parents naturels. Il s’agit de la première fois qu’un échange de nids a été documenté chez le faucon pèlerin sauvage.